Guamán Poma and the Hippocratic theory: From European iconography to the Andes - Pacheco Ibarra, Juan José (2010)
One of the influential factors of constructing the image of man in the New World was the Hippocratic vision, which was used to to explain the differences among indigenous peoples: their lifestyles, sickness, and moral customs. Chronicles such as Felipe Guaman Poma de Ayala and Martin de Murua would have been familiar with the Hippocratic-Galenic Theory and probably used its principles to picture Andean man, by means of texts, engravings and sketches that had spread through Europe. This article analyzes some sources that may have been used by Guaman Poma de Ayala to write his Nueva Corónica, especially the influence of the Hippocratic Theory in part of his work and how this theory served to construct an image of Andean man and his moral differences.